2016
DOI: 10.1002/hon.2322
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of IL‐10 receptor β affects the prognosis of multiple myeloma patients treated with thalidomide and/or bortezomib

Abstract: Interleukin-10 (IL-10) and IL-10 receptor (IL-10R) single nucleotide polymorphisms have been implicated in the pathogenesis of many cancers. We investigated the influence of IL-10 -592C/A, IL-10RA I224V, and IL-10RB K47E on the risk of developing multiple myeloma (MM) and the clinical features of MM. We extracted the genomic DNA from 128 MM patients and 202 healthy controls and used polymerase chain reaction-restriction fragment length polymorphism method to detect IL-10 promoter -592C/A (rs1800872), IL-10RA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Moreover, differences in survival were observed between subjects treated with thalidomide and/or bortezomib and those cured with conventional drugs. Their results suggest that IL-10 and IL-10R gene polymorphisms may not influence the predisposition to MM but may be correlated with the severity and prognosis of MM [ 212 ].…”
Section: Anti-inflammatory Cytokinesmentioning
confidence: 99%
“…Moreover, differences in survival were observed between subjects treated with thalidomide and/or bortezomib and those cured with conventional drugs. Their results suggest that IL-10 and IL-10R gene polymorphisms may not influence the predisposition to MM but may be correlated with the severity and prognosis of MM [ 212 ].…”
Section: Anti-inflammatory Cytokinesmentioning
confidence: 99%
“…IL-10 is a cytokine that regulates immune function, acting on a variety of immune cell subsets and playing a role in immune suppression in a variety of ways that can cause or prevent tumor immune escape. Recent studies reported that IL-10 also stimulates the immune response, suggesting that it is a multifunctional cytokine with positive and negative regulatory effects [24].…”
Section: Discussionmentioning
confidence: 99%
“…The published dates of all research studies varied from 2000 to 2018. Most of the research was conducted within Caucasian communities: 10 studies in Caucasian populations (62.5%) (20,22,23,25,(33)(34)(35)(36)(37)(38), 3 within Asian populations (18.75%) (17,39,40) and 3 in Mixed Afro-American populations (18.75%) (24,41,42). Of note, the quantitative TaqMan method (TaqMan PCR) was often used to detect the SNP state with control references (11 studies, 68.75%) (20,(22)(23)(24)(25)(36)(37)(38)(39)41,42).…”
Section: Study Selectionmentioning
confidence: 99%
“…Of note, the quantitative TaqMan method (TaqMan PCR) was often used to detect the SNP state with control references (11 studies, 68.75%) (20,(22)(23)(24)(25)(36)(37)(38)(39)41,42). Also, polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method was used in 5 studies (31.25%) (17,(33)(34)(35)40). The variables from sixteen relevant case-control studies were contained 2,597 cases and 3,851 controls.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation